Philippine maritime transport safety analysis of incidents over the last twenty years - Escarro, John Michael J.
The number of incidents related to maritime transport has steadily increased based on the records taken twenty years ago, having a study period of ten years; from the year 1991-2000. This paper investigates the effectiveness of the system in place, covering a twenty year scope; from 1991-2010. This aims to further improve the country's maritime transport system and serve as an overview for future studies. With the use of comparative analysis on incident reports and interviews from different agencies, it is seen that the majority of the changes made over the past ten years was upgrading existing port installments and rehabilitating safety aids throughout the country. This also includes memorandums issued to guide all seamen on proper protocol within the harbor. Data shows a trend that the frequency of incidents decreased for the entire country. However, the severity and loss of life as a result of these incidents did not decline. It is observed that limiting the categories to only the nature of the incident will not suffice for a proper conclusion due to conflicting results. It is also seen that the lack of a consistent compiling system for incident reports greatly impedes the formation of a more in-depth study. As a prerequisite, a database must first be established to have easier access to complete data. For more in-depth analyses to be made in the future, the scope of the parameters must be extended to include "human error" factors. Future analysis will be of multi-disciplinary in nature since it will involve analyses not only engineering in nature but also of system and protocol assessment and optimization. Safety analyses will then no longer be limited to immediate causes of incidents, but also incorporate investigations on different levels of safety within a designed procedure.